Compressive strength of palm oil clinker concrete due to different temperature of fire exposure - Vivien Necent, Vinsan (2017)
A study on Compressive strength of Palm Oil Clinker Concrete (POCC) due to expose of various burning temperature for an hour. The concrete produced by fully replacement of palm oil clinker in coarse aggregates. The POC obtain from local palm oil mill waste. POC Crushed in jaw crusher with desire size. The suitable size of POC for replacement of coarse aggregate was 12.75mm. Crushed POC sieve into size such as passing through 12.75mm sieve and retained at 4.75mm sieve. [1] The perfect design mix proportion with ration of 1:1.34:0.89, to increase the workability and also as a water reducing agent superplasticiser of Sika ViscoCrete® -2199 were added to the mixture with ratio of 0.013. The material was measured in Kilogram (Kg). For an adequate of furnace, the POCC cast into mould size of 100mm X 100mm X100mm. Cast sample were immerged in water for 28 days as water curing to achieve its full strength. The matured sample where burned at temperature 100°C, 200°C, 300°C ,400°C and 500°C with respective samples. The samples are burned in furnace. Burned samples are cool down at room temperature for a day before the compressive strength test. The compressive strength was recorded for conclude the objectives for this study. As a control sample unburned POCC was tested as initial compressive strength of POCC before burning process. The compressive strength of burned samples are compered to unburned POCC as a bench mark.